TRIP6 regulates neural stem cell maintenance in the postnatal mammalian subventricular zone. Issue 9 (21st July 2014) - Lai, Yun‐Ju; Li, Ming‐Yang; Yang, Cheng‐Yao; Huang, Kao‐Hua; Tsai, Jui‐Cheng; Wang, Tsu‐Wei
<x xml:space="preserve">Abstract</x> Background: Postnatal neurogenesis persists throughout life in the subventricular zone (SVZ)‐olfactory bulb pathway in mammals. Extrinsic or intrinsic factors have been revealed to regulate neural stem cell (NSC) properties and neurogenesis. Thyroid hormone receptor interacting protein 6 (TRIP6) belongs to zyxin family of LIM proteins, which have been shown to interact with various proteins to mediate cellular functions. However, the role of TRIP6 in NSCs is still unknown. Results: By performing double immunofluorescence staining, we found that TRIP6 was expressed by Sox2‐positive NSCs in embryonic and postnatal mouse forebrains. To study the function of TRIP6 in NSCs, we performed overexpression and knockdown experiments with neurospheres derived from postnatal day 7 SVZ. We found that TRIP6 was necessary and sufficient for self‐renewal and proliferation of NSCs, but inhibited their differentiation. To further investigate the mechanism of TRIP6 in NSCs, we performed Luciferase reporter assay and found that TRIP6 activated Notch signaling, a pathway required for NSC self‐renewal. Conclusions: Our data suggest that TRIP6 regulates NSC maintenance and it may be a new marker for NSCs. Developmental Dynamics 243:1130–1142, 2014. © 2014 Wiley Periodicals, Inc.